2017
DOI: 10.1016/j.shaw.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A Lower Level of Physically Demanding Work Is Associated with Excellent Work Ability in Men and Women with Neck Pain in Different Age Groups

Abstract: BackgroundThe aim of this study was to investigate which physical and psychosocial work demands were associated with excellent work ability in individuals with neck pain, and to investigate age and sex differences in these associations.MethodsThe study sample was obtained from the Statistics Sweden cross-sectional Work Environment survey and consisted of workers who reported neck pain after work (N = 3,212).ResultsThe findings showed an association between excellent work ability and self-reported low exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 49 publications
2
27
1
3
Order By: Relevance
“…First, PWA is perhaps too complex a factor to capture with a single-item question. Nonetheless, El Fassi repetitive movements and heavy muscular tasks (Oliv et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…First, PWA is perhaps too complex a factor to capture with a single-item question. Nonetheless, El Fassi repetitive movements and heavy muscular tasks (Oliv et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden approximately 23 % of workers report neck pain during the last three months. Of those reporting neck pain 63 % were women [51]. It has been shown that having neck pain is one risk factor for developing long-term sick leave [32].…”
Section: Workers With Neck and Upper Extremity Disordersmentioning
confidence: 99%
“…Various risk factors for sickness absence, apart from disease, have been explored and identified, including old age, being a woman, low socioeconomic status, poor self-rated health and previous history of sickness absence [88,89]. Factors at work, such as non-strenuous work and recuperation, have both been linked to lower levels of sickness absence and higher work ability [51,90,91].…”
Section: Sickness Absencementioning
confidence: 99%
“…Em um estudo com indivíduos com dor cervical, foi relatado que trabalhadores que estavam mais expostos a exigências físicas e duradouras provocavam estresse nos sistemas cardiovascular e musculoesquelético, o que estava relacionado a um maior grau de incapacidade ou desvantagem 26 . Essa poderia ser uma explicação para a associação encontrada no presente estudo entre a capacidade para o trabalho e o domínio dor física do OHIP-14, mesmo após ter sido controlada por variáveis sociodemográficas e de autopercepção.…”
Section: ▄ Discussãounclassified